Z-Pinch Study with Discharge Initiation by an Electron Beam. (December 2020) - Drozdovsky, A A; Sasorov, P V; Bogdanov, A V; Gavrilin, R O; Drozdovsky, S A; Kantsyrev, A V; Karpov, M A; Panyushkin, V A; Roudskoy, I V; Savin, S M
Abstract: We study the gas discharge process under conditions when a relativistic electron beam is injected into the discharge tube after applying a high-voltage pulse. As a result, a plasma channel is created, a breakdown occurs, and a discharge develops. Comparative experiments were performed at different gas pressures under discharge conditions with and without electron beam initiation. They showed significant differences, especially during pinching and further development of the discharge.